Effect of different parameters on mixture formation and flow field in simulations of an evaporative spray injection test case - Dias Ribeiro, Mateus [UNESP]; Bimbato, Alex Mendonça [UNESP]; Zanardi, Maurício Araújo [UNESP]; Balestieri, José Antônio Perrella [UNESP] (Springer Nature, 2018)
Direct injection plays an important role in the efforts to increase efficiency of modern engines, and the correct evaluation of the velocity and fuel mixture fraction fields is crucial for modeling combustion in fuel sprays. Therefore, a computational study has been performed to assess the effect of different parameters on the mixture formation and flow field in the simulation of a single jet of the engine combustion network (ECN) “Spray G” evaporative gasoline injection test case. The Lagrangian particle tracking (LPT) approach was tested within both Reynolds-averaged Navier–Stokes (RANS) and large eddy simulation (LES) frameworks, and the varieties were compared. Additional parameters that were considered include mesh resolution (0.75, 0.50, and 0.25 mm) and droplet breakup (Reitz–Diwakar, Reitz–KHRT, and Pilch–Erdman), as well as stochastic turbulent dispersion (O’Rourke) and stochastic collision (O’Rourke) models. Experimental penetration length data from both liquid and vapor phases were used to validate the 54 simulations performed within this study. Then, a series of analyses were performed to weigh the effect of each isolated parameter on the outcome of the simulations. Finally, three additional simulations were conducted to study specific issues of LES in fuel spray modeling. In this way, this study was able to make a qualitative comparison of the evaporative spray cloud shapes and the evaluation of spray statistics in terms of the iso-octane mixture fraction and droplet/slip velocities.
Keywords: Fuel spray; ICE; Lagrangian particle tracking; LES; RANS